Enhancing polymer electrolytes with carbon nanotube fillers: A promising frontier - Misenan, M. S. M.; Farabi, M. S. Ahmad; Akhlisah, Z. N.; Khiar, A. S. A. (ELSEVIER, 2025)
This review is about carbon nanotubes (CNTs) as fillers in conductive polymer electrolyte. In the beginning of the review, brief information regarding energy storage has been provided. A polymer-based membrane is used in the polymer electrolyte, which may need filler or functionalization to improve device performance. Fillers are additives that can reduce production costs while also enhancing a composite's surface morphology and a polymer's mechanical strength. Due to their superior chemical, mechanical, electrical, thermal, and structural capabilities, carbon nanotubes (CNTs) are commonly utilized as fillers or additions for conductive composites. CNTs exhibit good interfacial compatibility with the host polymer matrix in addition to being mechanically robust. The synthesis method of CNTs including laser vaporization, electric arc discharge technique and chemical deposition has been discussed. This review offers succinct information to the researcher who insists on enhancing the polymer electrolyte employing these prospective fillers, described with necessary values of characteristics measurement. Based on recent investigations, it also includes the unique characteristics of the CNT nanofillers about their chemical structure and electrochemical capabilities.
Keywords: Carbon nanotube; Polymer electrolyte; Filler; Composite; Energy stotage; CHEMICAL-VAPOR-DEPOSITION; FUEL-CELL APPLICATIONS; MULTIWALL CARBON; MECHANICAL-PROPERTIES; COMPOSITE MEMBRANES; FRACTURE-TOUGHNESS; FUNCTIONAL-GROUPS; CATALYTIC GROWTH; GRAPHENE; NANOCOMPOSITES; Chemistry; Materials Science